Integrating sustainable building technologies in public toilets design—a case of container toilet in Ningbo, China - GAO, Jianchao (2018)
In the background of the toilet revolution promoting the upgrading of public toilets in China, integrating sustainable building technologies in public toilets design has gradually become a new trend that will solve many problems existing in toilets. The application of technologies responds to the call of low carbon life, which has a beneficial impact on the environment. In addition, this work puts forward a collection of techniques to solve the problem of construction and use of public toilets. The methods used throughout this paper have undergone a feasibility assessment, including social acceptability, applicability of technology and materials, economic and industrial aspects, and environmental protection. It mainly uses the case study, questionnaire and software simulation to obtain the relevant data, to analyze and gain the conclusion during the whole process of research. Especially, the study is conducted in the cases of Ningbo container toilet. The project use second-hand container as the main building material combined with the solar energy technology, rainwater collecting technology and passive building technologies¬. Through data analysis and comparison, it is found that the public toilet design integrating sustainable building technology is verified to be able to achieve the desired goal of energy saving, high efficiency and sustainable development. With this project, the challenges of solving public toilet problems and applying sustainable building technologies for further research are also submitted.